Application of hot melt extrusion for improving bioavailability of artemisinin a thermolabile drug. (1st February 2018) - Kulkarni, C.; Kelly, A. L.; Gough, T.; Jadhav, V.; Singh, K. K.; Paradkar, A.
Abstract: Hot melt extrusion has been used to produce a solid dispersion of the thermolabile drug artemisinin. Formulation and process conditions were optimized prior to evaluation of dissolution and biopharmaceutical performance. Soluplus ®, a low T g amphiphilic polymer especially designed for solid dispersions enabled melt extrusion at 110 °C although some drug-polymer incompatibility was observed. Addition of 5% citric acid as a pH modifier was found to suppress the degradation. The area under plasma concentration time curve (AUC0–24h ) and peak plasma concentration ( C max ) were four times higher for the modified solid dispersion compared to that of pure artemisinin.